Analysis of Preventive Maintenance Line Dosing using Modularity Design and Mean Time Between Failure (MTBF) - Aries Firmansyah; Joumil Aidil Saifuddin Z.S (Manunggal Halim Jaya, 2026)
Maintaining operational continuity requires effective maintenance of production equipment. The dosing line at PT XYZ experienced a total downtime of 7,597 minutes between October 2024 and September 2025, indicating the need for a structured and data-driven maintenance strategy. This study aims to classify maintenance modules, identify failure root causes using a modularity design approach, determine optimal inspection intervals and preventive maintenance frequencies, and evaluate actual availability against standard availability based on mean time between failure (MTBF) and operational time. The dosing line was divided into six main modules, followed by root cause analysis and calculation of MTBF, inherent availability, and operational availability to determine optimal inspection intervals. The results indicate that failures are mainly caused by material blockages, pneumatic issues, component aging, and programmable logic control (PLC) disturbances. The dosing weight module requires the highest preventive maintenance frequency (71 times per year), with optimal inspection intervals ranging from 16 to 53 days across modules. All modules exceeded standard availability thresholds, with inherent availability above 99% and operational availability above 90%. These findings confirm that integrating modularity design and MTBF analysis effectively supports systematic and data-driven preventive maintenance planning.